Phenotypic heterogeneity in study populations may significantly confound the results of genetic association studies on alcohol dependence. (December 2015) - Ali, M. Adam; Way, Michael J.; Marks, Michael; Guerrini, Irene; Thomson, Allan D.; Strang, John; McQuillin, Andrew; Morgan, Marsha Y.
Abstract : Background: The interpretation of genetic studies on alcohol dependence may be confounded by the co-occurrence of substance dependence, psychiatric disorders and alcohol-related comorbidities, for example, cirrhosis. Significant single-marker and haplotypic associations between polymorphisms in the zinc finger gene, ZNF699, and alcohol dependence were reported in the Irish Affected Sib Pair Study of Alcohol Dependence population, one-third of whom had co-occurring substance dependence while 80% had identified psychiatric comorbidity. The aim of this study was to explore variant ZNF699 associations with alcohol dependence while exercising controls for potential confounders. Methods: The study population was comprised of 1449 alcohol-dependent cases and 1283 population controls; all were of British or Irish ancestry. None of the cases had a history of dependence on other substances, and the frequency of comorbid depression was low. A separate, ancestry-matched cohort of 196 opioid-dependent cases was also included. Genotyping for the four previously identified SNPs of interest in ZNF699 was performed using K-Biosciences Competitive Allele Specific PCR. Results: No single-marker associations were found between polymorphisms in ZNF699 and alcohol dependence per se. A significant allelic association was found between rs7254880 in ZNF699 and alcohol-related cirrhosis ( n =292), using cases with no biopsy evidence of liver disease ( n =314) as controls ( P =0.013). Significant allelic associations were also found between rs12460279 ( P =0.028), rs7252865 ( P =0.012) and rs10854142 ( P =0.016) in ZNF699 and opioid dependence. Conclusion: Phenotypic variation in study populations may contribute towards the nonreplication of genetic association studies on alcohol dependence; controls for recognised confounding variables should be exercised whenever possible. Abstract : Supplemental Digital Content is available in the text.